METAFORA DALAM TEKS BERITA HOAKS DI MEDIA SOSIAL: STUDI SEMANTIK KOGNITIF - Ardhianti, Mimas (Program Studi Pendidikan Bahasa Indonesia STKIP-PGRI Bangkalan, 2019)
This study aimed to describe the analysis of metaphor in the report text hoax in social media. The need of information is increasing, making the media increasingly developed into various forms and functions that enable people to meet their needs. For example, television and radio, which categorized as in electronic media. Newspapers, magazines, and tabloids in the category of print media, and online media in which there are the internet and social media. Meanwhile, in the online world, the more popular and have increased with news websites managed by the residents, and show news made by citizens, not by professional journalists. Internet access is widespread and increasingly inexpensive, allowing every citizen to participate in jurnalistic world, not only as a consumer of news, but also as newsmakers, including through the creation of personal web-blog. The problem in this research is the analysis of metaphors in hoax news in social media. Research using qualitative descriptive study. Sources of data in this study is hoax news text in which there are words, phrases, sentences, and paragraphs. From the results of analysis are structural metaphor, metaphor orientasional and ontological metaphors.